2019
DOI: 10.1371/journal.pone.0214236
|View full text |Cite
|
Sign up to set email alerts
|

Chlorothalonil induces oxidative stress and reduces enzymatic activities of Na+/K+-ATPase and acetylcholinesterase in gill tissues of marine bivalves

Abstract: Chlorothalonil is a thiol-reactive antifoulant that disperses widely and has been found in the marine environment. However, there is limited information on the deleterious effects of chlorothalonil in marine mollusks. In this study, we evaluated the effects of chlorothalonil on the gill tissues of the Pacific oyster, Crassostrea gigas and the blue mussel, Mytilus edulis after exposure to different concentrations of chlorothalonil (0.1, 1, and 10 μg L −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 71 publications
0
7
0
1
Order By: Relevance
“…This response may reveal the activation of a compensatory mechanism allowing for plasticity in response to moderate adverse environments [75]. Hormesis responses after exposure to organic compounds were also observed regarding other oxidative stress-related biomarkers in marine bivalves, such as CAT activity of Crassostrea gigas or GSH levels of M. edulis [76]. This enzyme plays a main role in regulating cholinergic neurotransmissions [77,78], therefore adverse effects on AChE may disrupt many essential nervous system functions.…”
Section: Discussionmentioning
confidence: 90%
“…This response may reveal the activation of a compensatory mechanism allowing for plasticity in response to moderate adverse environments [75]. Hormesis responses after exposure to organic compounds were also observed regarding other oxidative stress-related biomarkers in marine bivalves, such as CAT activity of Crassostrea gigas or GSH levels of M. edulis [76]. This enzyme plays a main role in regulating cholinergic neurotransmissions [77,78], therefore adverse effects on AChE may disrupt many essential nervous system functions.…”
Section: Discussionmentioning
confidence: 90%
“…Nussey et al [41] meanwhile suggested that osmotic adaptation was responsible for the decrease in serum K + . Te considerable alterations in Na + /K + -ATPase activity may explain why the blue mussel (Mytilus edulis) is unable to compete against the enhanced passive ion efux that occurs when it is exposed to the antifouling chemical chlorothalonil [42]. Some hematological changes were also associated to acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…GPx use the reduced form of GSH to decompose peroxides yielding GSSG which is regenerated through an active GR redox cycle (Regoli and Giuliani 2014). The increase in GR activity under stress conditions, linked to that of GPx, has been observed in different organisms (González-Fernández et al 2015;Haque et al 2019). Although CAT is predominant in H 2 O 2 detoxification, catalyzing the decomposition of H 2 O 2 into water and oxygen, GPx is the first antioxidant defense mechanism to be activated since it has more affinity than CAT to H 2 O 2 (Vidal-Liñán et al 2010).…”
Section: Discussionmentioning
confidence: 99%